The Relationship between Employee Well-being, Work-life Balance, Job Stress and Turnover Intention Among SMEs in Johor - Tan, Chee Peng; Salahudin, Shahrul Nizam (Research in Management of Technology and Business, 2025)
The objective of this study is to examine the relationship between employee well-being, work-life balance, job stress, and turnover intention among small and medium-sized enterprises (SMEs) in Johor. A quantitative methodology was utilized to gather data by conducting surveys among employees from several small and mediumsized enterprises (SMEs) in Johor.The data was studied using descriptive and inferential statistical techniques to comprehend the interconnections among the variables under investigation.The focus of this study is on individuals who are engaged in Small and Medium-sized Enterprises (SMEs) in Johor, Malaysia. The data will be analyzed using the Statistical Package for Social Science (SPSS). The results indicate a relationship between employee well-being ,work-life balance, job stress and turnover intention. These findings indicate that improving the well-being and work-life balance of employees can lower workplace stress levels and reduce the likelihood of SME employees in Johor wanting to quit their jobs. This study offers significant insights for employer of small and medium-sized enterprises (SMEs) and policymakers in creating successful methods to boost employee well-being, promote work-life balance, and alleviate job stress to reduce employee turnover rates.